Flexible Tactile Electronic Skin Sensor with 3D Force Detection Based on Porous CNTs/PDMS Nanocomposites - Sun, Xuguang (Nanomicro Lett, 2019)
Flexible tactile sensors have broad applications in human physiological monitoring, robotic operation and human–machine interaction. However, the research of wearable and flexible tactile sensors with high sensitivity, wide sensing range and ability to detect three-dimensional (3D) force is still very challenging. Herein, a flexible tactile electronic skin sensor based on carbon nanotubes (CNTs)/polydimethylsiloxane (PDMS) nanocomposites is presented for 3D contact force detection. The 3D forces were acquired from combination of four specially designed cells in a sensing element. Contributed from the double-sided rough porous structure and specific surface morphology of nanocomposites, the piezoresistive sensor possesses high sensitivity of 12.1 kPa(−1) within the range of 600 Pa and 0.68 kPa(−1) in the regime exceeding 1 kPa for normal pressure, as well as 59.9 N(−1) in the scope of < 0.05 N and > 2.3 N(−1) in the region of < 0.6 N for tangential force with ultra-low response time of 3.1 ms. In addition, multi-functional detection in human body monitoring was employed with single sensing cell and the sensor array was integrated into a robotic arm for objects grasping control, indicating the capacities in intelligent robot applications. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40820-019-0288-7) contains supplementary material, which is available to authorized users.